Review of Digital Construction of UHV Projects Based on Building Information Modeling Technology - QI Lizhong, LIU Ding, ZHANG Zhuoqun, XIE Rongzhen, RONG Jingguo, ZHANG Su, YUAN Bo, SUN Yi (Dianli jianshe)
As major national infrastructure projects， UHV projects are key to ensuring power grid security， promoting energy consumption， and optimizing resource allocation. To better meet the requirements of "large-scale centralized construction， high-intensity innovation and research， and high-quality transformation and upgrading" of UHV projects， conducting digital construction of UHV projects based on building information modeling （BIM） technology is imperative. First， this study focuses on the construction of a BIM standard system for UHV projects， designs the framework of the standard system， and discusses the expansion and improvement of the standard system. Subsequently， the construction status of BIM management and control platforms for UHV projects are introduced， and the functions and applications of the subsystems are summarized. Finally， this study analyzes typical application scenarios of BIM technology in the design and construction stages of UHV projects. Based on the current application status of BIM technology in the design， construction， and operation stages of UHV projects， this study summarizes its applicability and practical results and provides experience and suggestions for the digital construction of UHV projects.